Ambroxol Hydrochloride Combined with Fluconazole Reverses the Resistance of Candida albicans to Fluconazole - Li, Xiuyun; Zhao, Yuanhao; Huang, Xin; Yu, Cuixiang; Yang, Yilei; Sun, Shujuan (Frontiers in Cellular and Infection Microbiology, 2017)
In this study, we found that ambroxol hydrochloride (128 μg/mL) exhibits synergistic antifungal effects in combination with fluconazole (2 μg/mL) against resistant planktonic Candida albicans cells. This combination also exhibited synergistic effects against resistant Candida albicans biofilms in different stages (4 h, 8 h and 12 h) according to the microdilution method. In vitro data were further confirmed by the success of this combination in treating Galleria mellonella infected by resistant Candida albicans. With respect to the synergistic mechanism, our result revealed that ambroxol hydrochloride has an effect on the drug transporters of resistant Candida albicans, increasing the uptake and decreasing the efflux of rhodamine 6G, a fluorescent alternate of fluconazole. This is the first study to investigate the in vitro and in vivo antifungal effects, as well as the possible synergistic mechanism of ambroxol hydrochloride in combination with fluconazole against resistant Candida albicans. The results show the potential role for this drug combination as a therapeutic alternative to treat resistant Candida albicans and provide insights into the development of antifungal targets and new antifungal agents.